Statistical Tests for Replacement Blocks Assessment - Chugunkov, Ilya V.; Kliuchnikova, Bogdana V.; Riakhovskaia, Iuliia S.; Chugunkov, Vladimir I. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2021)
The basic operations of the round function of any block cipher are substitution and permutation. The article discusses approaches to the implementation of the replacement operation. The main cryptographic primitive, namely the block of substitutions or S-block, and its variations, such as, the R-block, are considered. Requirements for a high-quality substitution block are formulated. The approaches to the assessment of replacement blocks are analyzed. Methods to improve their efficiency are proposed. Forecasts for the development of replacement blocks are made.